The Relationship of Metabolic Syndrome Traits with Beta-Cell Function and Insulin Sensitivity by Oral Minimal Model Assessment in South Asian and European Families Residing in the Netherlands - Thekla Geragotou; Sjaam Jainandunsing; Behiye Özcan; Felix W. M. de Rooij; Alexander Kokkinos; Nicholas Tentolouris; Eric J. G. Sijbrands (Journal of Diabetes Research)
Background. There are different metabolic syndrome traits among patients with different ethnicities. Methods. We investigated this by studying 44 South Asians and 54 Europeans and classified them in three groups according to the occurrence of metabolic syndrome (MetS) and Type 2 Diabetes (T2D). Insulin sensitivity index (ISI), static, dynamic, and total beta-cell responsivity indices (Φ), and disposition indices (DIs) were calculated with the use of oral minimal model (OMM). Results. In both ethnicities, ISI was lower in the subgroup with MetS and T2D as compared to the subgroup without MetS nor T2D (P<0.004). South Asians without MetS were more insulin resistant than Europeans without MetS (P=0.033). In the South Asians, ISI, dynamic DI, and static DI were associated significantly (P<0.006) with high-density lipoprotein cholesterol and triglycerides. In the Europeans, ISI was associated with waist-to-hip ratio (P=0.005) and systolic and diastolic blood pressure (P<0.005), while static DI was related to the systolic blood pressure (P=0.005). Conclusions. MetS was linked with insulin resistance and reduced capacity to handle glucose regardless of ethnicity. ISI and DIs were associated with lipid traits in South Asians and with blood pressure in Europeans suggesting that insulin resistance enhances different metabolic syndrome traits among different ethnicities.